ضمائر السّرد في الرّواية الجزائريّة المعاصرة (رواية " تميمون" لرشيد بوجدرة، و " البطاقة السّحرية " لمحمّد ساري أنموذجا) - زاغز, نزيهة; مكدور, عبد اللطيف (جامعة الوادي - university of Eloued, 2021)
لا تخلو الرواية الجزائريّة المعاصرة من تعدّد وتنوّع ضمائر السّرد فيها على عكس ما كان سائدا في الرّواية التّقليدّية، إذ نجد السرد فيها ينتقل من ضمير إلى آخر، فيتلاعب بها الروائي على مستوى المتن الحكائي، فيجعلها كأنّها تنطق بلسان رواة كثر، إنّ هذا التنوّع يلجأ إليه الروائي عمدا لأنّ كل ضمير له أهميّة ووظيفة يؤديها في البناء السّردي. وعليه فإنّ مقالنا هذا يسعى لرصد هذه الضّمائر الثلاثة وتحديد أغراضها ووظائفها المختلفة في روايتي " تيميمون " و " البطاقة السّحريّة " اللّتين اتخذناهما أنموذجا لهذه الدّراسة. الكلمات المفتاحية: ضمائر؛ سرد؛ اعتراف؛ رؤية سردية؛ سارد. Abstract: The contemporary Algerian novel is not without the multiplicity and diversity of narrative pronouns in it, unlike what was prevalent in the traditional novel. In which we find the narrative moves from one pronoun to the other. And the novelist intentionally plays with it at the storytelling body. Therefore he makes it as if it speaks on behalf of many narrators. This diversity is purposefully sought by the author because every pronoun has an importance and a function that it performs in the narrative construction. Therefore, our article seeks to monitor these three pronouns and define their various purposes and functions in the two novels "Timimoun" and "The Magic Card", which we have taken as a model for this study. key words :pronouns ; narration; confession; narrative vision; narrator.
مقال
Keywords: ضمائر ; سرد ; اعتراف ; رؤية سردية ; سارد